Assessment of the Physical Condition of Students of a Special Medical Group for Physical Education of The National University of Uzbekistan (Texas Journal of Multidisciplinary Studies, 2022)
One of the main factors of a healthy lifestyle of a modern person is rational motor activity that significantly improves physical health, especially the state of the musculoskeletal and cardiovascular systems, improves immunity, and has a positive effect on the general tone of a person. Therefore, universities pay special attention to sports and recreation technology, which is a way to implement activities aimed at achieving and maintaining physical well-being and reducing the risk of developing diseases.